Compensation against Fuel Inflation: Temporary Tax Rebates or Transfers? - Odran Bonnet; Étienne Fize; Tristan Loisel; Lionel Wilner (Center for Economic Studies and ifo Institute (CESifo), 2024)
This article exploits both the crude oil price surge consecutive to the invasion of Ukraine and 2022 fuel excise tax rebates in France as quasi-natural experiments to infer the price sensitivity of fuel demand. Based on granular individual bank account data at the transaction level, we properly disentangle anticipation effects from price effects, and estimate an average price elasticity of -0.31. It varies little with respect to income and location but substantially decreases, in absolute, with respect to fuel spending and is higher for retirees. We evaluate financial and distributional effects of the actual tax policy as well as its impact on CO2 emissions based on counterfactual simulations. We empirically demonstrate that resorting to transfers, be they targeted or not, achieves only imperfect compensation against fuel inflation. However, we show that a policy maker subject to a tight budget constraint and seeking to alleviate excessive losses, relative to income, prefers means-tested transfers to rebates.
Keywords: C18; C51; D12; H23; H31; L71; Q31; Q35; Q41; 330; commodity taxation; excise tax; tax-and-transfer schemes; fuel price elasticity; anticipatory behaviour; transaction-level data